Clinical Outcomes of Femtosecond Laser-assisted Implantation of 325-Degree Versus 340-Degree Arc Length Intracorneal Ring Segments in Naive Keratoconic Eyes - Amir Faramarzi; Kiana Hassanpour; Marjan Mazouchi; Bahram Einollahi; Sepehr Feizi; Hamed Esfandiari; Mohammad-Mehdi Sadoughi; Majid Moshirfar (Journal of Ophthalmic & Vision Research, 2023)
Abstract Purpose: To evaluate and compare clinical outcomes after femtosecond laser-assisted implantation of 325-degree versus 340-degree arc length intracorneal ring segments (ICRS) in eyes with keratoconus (KCN). Methods: In this prospective non-randomized interventional case series, 23 eyes of 21 patients diagnosed with KCN, underwent femtosecond laser-assisted implantation of two types of ICRS, which included a 325-degree ICRS (Group 325) and a 340-degree ICRS (Group 340). The primary outcome measures were uncorrected distance visual acuity (UDVA), and the secondary outcome measures included corrected distance visual acuity (CDVA), sphere, cylinder, mean refractive spherical equivalent (MRSE), keratometry, vectorial change in corneal astigmatism, and the location of maximum keratometry relative to the corneal apex. The study groups were compared using the primary and secondary outcome measures obtained at postoperative months six and 12. Results: Groups 325 and 340 consisted of 10 and 13 eyes, respectively. The two groups were comparable in terms of parameters measured preoperatively. On comparison to the baseline values, both study groups exhibited a significant increase in UDVA and CDVA measured at postoperative month six (Ps < 0.05) and a significant decrease in the sphere, cylinder, spherical equivalent refraction, and keratometry readings measured at postoperative months six and 12 (Ps < 0.05). No significant differences were observed between the two groups in terms of visual, refractive, and keratometric outcomes at any time point. No intraoperative or postoperative complications were observed in any of the study groups. Conclusion: Both the 325-degree ICRS and the 340-degree ICRS effectively and equally improved visual, refractive, and keratometric outcomes in keratoconic eyes.